BIMBINGAN LITERASI KEUANGAN SEJAK DINI SEBAGAI UPAYA MEMBANGUN BUDAYA MENABUNG PADA SISWA DI DESA BULU SUGIHWARAS BOJONEGORO - Faizin, Muhammad; Sugito, Sugito; Kamaliya, Niha; Marsanda, Meliy; Chofifah, Ulya; Virnanda, Nandita Aprilia Ayu; Sya’diyah, Lailatus; Yuliana, Widya Ayu; Ilmy, Rintan Aulal; Ma’rifah, Siti; Arfianda P A, Velly Ika; Soimah, Siti Maghfirotin; Cahyatilmasamah, Sofia; Ruslina, Ayuni (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This study aims to analyze the effectiveness of early financial literacy guidance activities in fostering a saving culture among elementary school students in Bulu Village, Sugihwaras, Bojonegoro. Using a descriptive-quantitative approach, the study measures changes in students’ knowledge, attitudes, and saving behavior after participating in the program. Data were collected through observation, pretest–posttest questionnaires, and teacher and parent assessments using a Likert scale. The results show a significant increase in students’ knowledge and attitudes toward financial literacy, with the average pretest score rising from 62.8 to 83.5 in the posttest (p-value = 0.001 < 0.05). This indicates that the guidance activities positively influenced students’ understanding and attitudes in managing their pocket money. In terms of saving behavior, 78.3% of students began saving regularly with an average weekly balance of IDR 12,000. This behavioral change is also reflected in the increased frequency of saving, consistency in maintaining savings, and the ability to set simple financial goals. In addition to the impact on students, the program also received positive responses from teachers and parents. The average teacher satisfaction score reached 4.47, while parental support scored 4.04. The highest-rated aspects among teachers were the material (4.83) and the program’s results (4.76), while parents gave the highest score to the results (4.59). These findings indicate that the financial literacy guidance was perceived as relevant, engaging, and impactful in changing students’ behavior. The implications of this study show that early financial literacy education not only enhances knowledge but also fosters responsible financial character through sustainable saving habits. The program’s success was supported by collaboration among schools, teachers, and parents, contributing to the strengthening of economic character education in elementary schools. Evaluation through weekly savings monitoring, pretest–posttest comparisons, and reflections from teachers and parents showed that the program effectively instilled values of discipline, responsibility, and financial awareness in children. Thus, the activity successfully established a sustainable saving culture as the foundation for healthy economic behavior among the younger generation.